STUDI KASUS PUTUSAN PENGADILAN NEGERI BANDUNG NOMOR 574 TAHUN 2020 TENTANG ANAK YANG BELUM DEWASA TERLIBAT NARKOBA - Milda Anggraeni N; Sholla Daifina F; Naufal Rafas Sultan; Serllyta Nova Ramadhan (Cross-border, 2022)
Based on case number 574 of 2020, the Bandung District Court against a young man who was involved in drugs and was legally and convincingly proven guilty of committing the offense of "Demanding, storing, controlling, or giving Narcotics Group I is not a plant", as regulated and should be punished in Article 112 paragraph (1) Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics, according to the Case Study of the Decision of the Bandung District Court Number 574 of 2020 against young children involved with drugs. The purpose of this study is to find out how judges consider the law in making decisions against children related to drugs and to see how the law guarantees for teenagers as perpetrators of drug offenses and how the juridical examination of drug crimes against young people who fall into drugs. In analyzing this research, the methodological strategy used is qualitative technique, in particular by utilizing information gathering procedures that are carried out in an integrated manner by emphasizing the importance of generalization. The conclusion in this study is that the judge's considerations in passing his legal decision on minors involved in drugs in the case of choice of court number 574 of 2020 Bandung District Court regarding minors related to drugs and proven valid and convincingly wrong, and legal protection for adolescents as perpetrators of treatment violations where children who are bound to drugs are required to receive supervision, action, treatment, and recovery by the public and local authorities as well as a juridical examination of criminal decisions against children involved in drugs. With related regulations which in the Child Protection Law Number 23 of 2002 article 59 says that children who are bound in drug addiction should be the government and other foundations are obliged to be responsible for providing special guarantees to teenagers.